O11 UK national service evaluation of transplant assessments for patients with alcohol-related liver disease. (20th September 2022) - Oldroyd, Christopher; Wai, Clare; Holt, Andrew; Rajoriya, Neil; Masson, Steven; Chew, Yun; Parker, Richard; Ryan, Jennifer; Shepherd, Liz; Simpson, Kenneth; Aluvihare, Varuna; Webzell, Ian; et al.
Abstract : Background: Alcohol-related liver disease (ArLD) accounts for the majority of liver-related death and is the most common indication for liver transplant in the UK1. There is no systematic data collection for patients who are being assessed for liver transplantation until the point of entry to the waiting list1. This study aimed to collect detailed information from patients during the assessment stage. Method: Data were collected prospectively for all patients with a diagnosis of ArLD assessed for liver transplant at the seven UK liver transplant centres from 1st Aug 2020 to 31st July 2021. Data included: gender, age category, postcode (first half), indication for transplant, Model for End-Stage Liver Disease Score (MELD), United Kingdom Model for End-Stage Liver Disease Score (UKELD), co-factors for liver disease, duration of abstinence, listing decision and reasons for decline or deferral. We looked for any differences between patients listed for transplant and those not listed. Results: 549 patients were included ( table 1 ). Median UKELD was 54 (range 41–76) and median MELD was 15 (range 4–39). 134 patients (24%) were female. Using postcode data a map was produced demonstrating approximate locations of included patients (Image 1). Median duration of abstinence was 12 months (range 0–240), with 14% of assessments having ≤6 months abstinence. 326 (59%) patients were listed for transplantation, with 202 (37%) not listed, and 21 (4%) deferred. Indications for transplant assessment were: UKELD≥49 (90%), ascites (31%), hepatic encephalopathy (18%), hepatocellular carcinoma (16%) and other (11%) with most patients having multiple indications. The most common co-factor was non-alcoholic steatohepatitis (n = 58) with hepatitis C virus infection second most common (n = 23). Most common reasons for not listing were: medical co-morbidities (30%), too early to need transplant (20%), potential recoverability (18%), active or recent alcohol use (12%), concern about return to harmful drinking (8%) and surgical risk (5%) ( figure 1 ). Comparing patients listed for transplant with those not listed we noted higher UKELD (p < 0.001) and MELD (p < 0.001). Patients with ascites were less likely to be listed than those without (49.7% vs 66.8% p < 0.001). There were no significant differences in listing rates based on age, gender, short (< 6 months) vs long (>6 months) period of abstinence, or on any other parameters. Conclusion: This study provides for the first time a profile of all patients with ArLD assessed for liver transplantation over a 12-month period in the UK. Reference: NHS Blood and Transplant. Annual Report on Liver Transplantation. Report for 2020/21. Available: https://nhsbtdbe.blob.core.windows.net/umbraco-assets-corp/24593/nhsbt-liver-transplant-report-2021-final.pdf